2001
DOI: 10.1046/j.1365-2435.2001.00505.x
|View full text |Cite
|
Sign up to set email alerts
|

Population divergence in the plasticity of the response of Quercus coccifera to the light environment

Abstract: Summary  Quercus coccifera, a slow‐growing, evergreen oak, grows in contrasting environments in the Mediterranean Basin. Habitat‐based selection may have promoted divergence between populations with respect to phenotypic plasticity and genetic variability.  We tested the hypothesis that populations of the Q. coccifera originating from a rock outcrop, a continental garrigue formation and an oceanic forest would differ in their plastic response to light intensity. Plants from these populations were grown from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(31 citation statements)
references
References 55 publications
5
25
0
1
Order By: Relevance
“…The results found in this study show that the ecological origin of the populations determined their capacity for light acclimation. Blaguer et al (2001) also found that populations of Q. coccifera, an evergreen oak originating from different localities in the Mediterranean, differ in their plastic response to light intensity. They concluded that differences among populations suggested an ecotypic differentiation towards less phenotypic plasticity in the most homogeneous light environments (Blaguer et al 2001).…”
Section: Intraspecific Differences In Response To High Lightmentioning
confidence: 85%
See 3 more Smart Citations
“…The results found in this study show that the ecological origin of the populations determined their capacity for light acclimation. Blaguer et al (2001) also found that populations of Q. coccifera, an evergreen oak originating from different localities in the Mediterranean, differ in their plastic response to light intensity. They concluded that differences among populations suggested an ecotypic differentiation towards less phenotypic plasticity in the most homogeneous light environments (Blaguer et al 2001).…”
Section: Intraspecific Differences In Response To High Lightmentioning
confidence: 85%
“…Blaguer et al (2001) also found that populations of Q. coccifera, an evergreen oak originating from different localities in the Mediterranean, differ in their plastic response to light intensity. They concluded that differences among populations suggested an ecotypic differentiation towards less phenotypic plasticity in the most homogeneous light environments (Blaguer et al 2001). More recently, Aranda et al (2005) found differences in cold tolerance among populations of cork oak.…”
Section: Intraspecific Differences In Response To High Lightmentioning
confidence: 85%
See 2 more Smart Citations
“…Different studies showed a possible intraspecific variability and phenotypic plasticity in Cork oak as an adaptation to contrasting regional climate conditions (Balaguer et al 2001, Aranda et al 2005, Staudt et al 2008, Ramirez-Valiente et al 2010, Matesanz & Valladares 2014, Gratani 2014. Investigating the influence of full-sun on seedling hardiness, Calzavara et al (2015) suggested that the acclimation process can induce changes in physiological, anatomical, and morphological traits of plants, favoring their establishment after transplantation to the field.…”
Section: Discussionmentioning
confidence: 99%